2019
DOI: 10.21448/ijsm.484954
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt+Salt-Stressed Salvia officinalis: ROS Scavenging Capacity and Antioxidant Potency

Abstract: Salvia officinalis L. (Lamiaceae) is one of the most widespread herbal species used in the food processing industry and for culinary and medicinal purposes. This work aimed to investigate changes in plant growth, water content, lipid peroxidation, H2O2, proline, and enzymes related to reactive oxygen species (ROS) detoxification including superoxide dismutase (SOD), peroxidase (POX), catalase (CAT), ascorbate peroxidase (APX) and glutathione reductase (GR). Phenolic contents and antioxidant capacity values suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
1
3
0
4
Order By: Relevance
“…In comparison with the control (55.73%), the highest and the lowest DPPH radical scavenging activity was observed in 50 mM Sn (63.8%) and 50 mM Cu (34.8%) treated plants respectively. In a study (40), a 57.8% increase in the antioxidant activity was observed after 500 μM CoCl2 treatment in Salvia officinalis and in a study (46), after 15 days exposure of Colobanthus quitensis to 150 and 300 µM of copper sulphate, an induction in antioxidant activity by DPPH radical scavenging was observed in in vitro culture. A rise in DPPH activity was observed after 70 and 140 mg/L copper treatment in G. procumbens (25).…”
Section: Phosphomolybdate Metal Chelating and Dpph Radical Scavenging Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…In comparison with the control (55.73%), the highest and the lowest DPPH radical scavenging activity was observed in 50 mM Sn (63.8%) and 50 mM Cu (34.8%) treated plants respectively. In a study (40), a 57.8% increase in the antioxidant activity was observed after 500 μM CoCl2 treatment in Salvia officinalis and in a study (46), after 15 days exposure of Colobanthus quitensis to 150 and 300 µM of copper sulphate, an induction in antioxidant activity by DPPH radical scavenging was observed in in vitro culture. A rise in DPPH activity was observed after 70 and 140 mg/L copper treatment in G. procumbens (25).…”
Section: Phosphomolybdate Metal Chelating and Dpph Radical Scavenging Activitymentioning
confidence: 88%
“…In a study (27), flavonoid content in the shoots was found to increase in 250 μmol L -1 Cu treated Solanum lycopersicum while it was found to decrease in 250 μmol L -1 Cu treated Solanum cheesmaniae. An increase in TFC and TPC was observed in Salvia officinalis under 500 μM CoCl2 treatments as compared to control (40). In plants, flavonoids are located in mesophyll cells that act as a defense system against different stresses.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoids Content (Tfc)mentioning
confidence: 94%
“…Tuzluluk, dünyanın birçok bölgesindeki tarımsal üretim alanlarında toprak verimini, bitki büyümesini, verim ve kalitesini etkileyen, tarımsal sürdürülebilirliği zorlaştıran önemli sorunlardan biridir (Aziz ve ark., 2013;Torun, 2019). Tuzluluk yağış oranının yetersiz, buharlaşmanın fazla olduğu, kurak ve yarı kurak ekolojilerde sıkça görülmektedir.…”
Section: Tuz Stresine Karşı İndüklenen Yanıtlarunclassified
“…Bu türde tuz stresi altında salisilik asit tarafından arttırılan karbonhidrat konsantrasyonunun, tuz stresinin neden olduğu su kıtlığı nedeniyle oluşan oksidatif hasarın önlenmesine ve protein yapısının korunmasına yardımcı olduğu bildirilmiştir. Ayrıca serbest amino asitlerin, özellikle de salin koşullarda enerji ve nitrojen rezervuarı olarak işlev yapan prolinin üretimi ve birikimi Salvia officinalis'in tuz stresine karşı geliştirdiği adaptif bir tepki olarak değerlendirilmiştir (Sahar ve ark., 2011;Torun, 2019).…”
Section: Tuz Stresine Karşı İndüklenen Yanıtlarunclassified
See 1 more Smart Citation